Psikologi Pendidikan Islam dalam al-Qur'an - Sudiarto Sudiarto; Siti Rohimah (TSAQOFAH, 2026)
The Qur’an, as the primary source of Islamic teachings, gives great attention to the cultivation of the human soul through various psychological concepts, such as nafs, qalb, ‘aql, and ruh. This article aims to examine the concept of human psychology from the perspective of the Qur’an, explain the principles of Islamic educational psychology contained therein, analyze the views of scholars, particularly Imam Al-Ghazali and Ibn Qayyim Al-Jawziyyah, and describe its implications for the educational process. This study uses a library research method with a descriptive-analytical approach. The results of the study show that the concept of psychology in the Qur’an includes three main principles, namely the principle of fitrah, tazkiyatun nafs or purification of the soul, and the use of reason in learning. Classical scholars emphasize that Islamic education must focus on the cultivation of the heart, purification of the soul, and holistic development of morality. The conclusion of this study affirms that Islamic educational psychology from the perspective of the Qur’an positions humans as multidimensional beings who have spiritual, intellectual, moral, and emotional dimensions that need to be developed in a balanced manner. Its practical implications show that Islamic education needs to pay attention to soul cultivation, strengthening of reason, and formation of noble character in order to form students who are not only intellectually intelligent but also have a balanced personality and are oriented toward achieving insan kamil.